Acute kidney injury among salicylate intoxication hospitalisations in the United States. Issue 3 (27th October 2020) - Thongprayoon, Charat; Petnak, Tananchai; Kaewput, Wisit; Qureshi, Fawad; Mao, Michael A.; Pivovarova, Aleksandra I.; Boonpheng, Boonphiphop; Bathini, Tarun; Vallabhajosyula, Saraschandra; Medaura, Juan; Cheungpasitporn, Wisit
Abstract: Background: This study aimed to evaluate the risk factors and the association of acute kidney injury (AKI) with outcomes, and resource utilisation in patients hospitalised because of salicylate intoxication in the United States. Methods: Hospitalised patients with a primary diagnosis of salicylate intoxication from 2003 to 2014 were identified in the National Inpatient Sample (NIS) database. End‐stage kidney disease patients were excluded. The occurrence of AKI was identified using hospital diagnosis code. Clinical characteristics, in‐hospital treatment, outcomes and resource utilisation were compared between patients with and without AKI. Results: A total of 13 787 eligible hospital admissions were included in the analysis. AKI occurred in 1279 (9.3%) admissions. Older age, male sex, more recent year of hospitalisation, anaemia, hypertension, congestive heart failure, chronic kidney disease, volume depletion, sepsis and ventricular arrhythmia/cardiac arrest were significantly associated with increased risk of AKI, whereas Hispanic race was associated with decreased risk. AKI was significantly associated with increased risk of organ failure, and in‐hospital mortality. In addition, the need for ventilation support, blood component transfusion, renal replacement therapy, length of hospital stay and hospitalisation cost were higher in AKI patients. Conclusion: Approximately one tenth of salicylate intoxication patients developed AKI during hospitalisation. AKI was associated with higher morbidity, mortality and resource utilisations.